Effects of early sub‐therapeutic antibiotic administration on body tissue deposition, gut microbiota and metabolite profiles of weaned piglets. (6th May 2022) - Hou, Lei; Cao, Shuting; Qiu, Yueqin; Xiong, YunXia; Xiao, Hao; Wen, Xiaolu; Yang, Xuefen; Gao, Kaiguo; Wang, Li; Jiang, Zongyong
Abstract: BACKGROUND: This study aimed to evaluate the effects of sub‐therapeutic antibiotic (STA) administration and its subsequent withdrawal on the body tissue deposition, gut microbiota, and metabolite profiles of piglets. The piglets in the experimental group were fed with STA (30 mg kg −1 bacitracin methylene disalicylate, 75 mg kg −1 chlortetracycline, 300 mg kg −1 calcium oxytetracycline) for 14 days and the target bodyweight of the withdrawal period was 25 kg. RESULTS: The experiment was divided into two periods: the administration period and the withdrawal period. The results showed that STA did not improve piglets' growth performance during the two periods. Piglets treated with STA had lower body water deposition during the withdrawal period and tended to increase body lipid deposition during the withdrawal period and the whole period in comparison with the piglets in the control group. It was found that STA markedly altered the colonic microbiota and their metabolites in the piglets. Sub‐therapeutic antibiotics were initially effective in decreasing the abundance of pathogenic bacteria during the administration period; however, STA could not continue the effect during the withdrawal period, leading to a rebound of pathogenic bacteria such as Alloprevotella and the increased abundance of other pathogenic bacteria like Oscillibacter . Remarkably, STA treatment decreased Blautia abundance. This bacterium plays a potential protective role against obesity. Metabolomic analysis indicated that STA mainly altered amino acid metabolism, lipid metabolism, and carbohydrate metabolism during the two periods. Spearman's correlation analysis showed that the gut microbiota was highly correlated with microbial metabolite changes. CONCLUSION: These results suggest that early STA administration may alter body tissue deposition later in life by reshaping the gut microbiota and their metabolite profiles. © 2022 Society of Chemical Industry.